Metodología para la valoración de riesgo país para los casos de : Brasil, Chile, Colombia, México y Perú (2017)
In this article, we propose a methodology to measure country risk taking into account the relationship between economic variables, and the performance of CDS (Credit Default Swaps). To achieve this, five emerging countries with similar economic characteristics were taken as reference: Brazil, Chile, Colombia, Mexico and Peru; With the purpose of demonstrating the differences of the determining factors when analyzing country risk. An econometric model was constructed for each country taking into account the exchange rate difference of each one. It was estimated by OLS (Ordinary Least Squares) having three different dependent variables per country to simulate short term, medium term and long term. It was found that each country has differences in the incidence of independent variables. In addition, the variables have a change in their significance, magnitude, and therefore in the way they are interpreted in each country.